HALP Score as a Prognostic Factor of Mortality in Septic Patients at Dr. Sardjito General Hospital - Anjani, Alindina; Asdie, Rizka Humardewayanti; Wijisaksono, Doni Priambodo (Faculty of Medicine Universitas Gadjah Mada, 2021)
Background. Sepsis is still an important health problem with a high mortality rate, an average of 44.5% in Asian countries. An easy and early biomarker is needed to determine the prognosis of sepsis. The HALP inflammation index can be used to predict mortality in malignancy conditions, yet has not been studied for sepsis.Objective. This study aimed to determine whether HALP score has a prognostic value for mortality in non malignant septic patients at Dr. Sardjito General Hospital.Methods. This was a retrospective cohort study of septic patients admitted to Internal Medicine wards between January 1, 2016 and December 31, 2018. The prognostic accuracy was evaluated by assessing the area under the receiver operating characteristic (AUC) curve. The primary outcome was mortality at the end of hospitalization. Results:. There were 125 adult patients, 104 with high HALP score (≥54,34), 21 low HALP score (<54,34), 45 patients died (36%). Patients with low HALP score were significantly at risk of death (p=0.007, OR 3.66, 95% CI 1.38-9.68) than high HALP score. Logistic regression was used to account for potential confounding factors. Low HALP score (p = 0.004, OR 4.74, 95% CI 1.63-13.76), sepsis diagnosed with quick SOFA (p = 0.006, OR 0.25, 95% CI 0.09-0.68), and multiple infections (p = 0.011, OR 2.93, 95% CI 1.28-6.73) were significantly associated with mortality in sepsis patients at Dr. Sardjito General Hospital.Conclusion. HALP score has a prognostic value of mortality in adult patients with sepsis at Dr. Sardjito General Hospital